The Routledge research companion to travel writing - Pettinger, Alasdair, 1959-; Youngs, Tim, 1961- (Routledge, 2020)
Showcasing established and new patterns of research, The Routledge Research Companion to Travel Writing takes an interdisciplinary approach to scholarship and to travel texts themselves. The volume adopts a thematic approach, with each contributor considering a specific aspect of travel writing - a recurrent motif, an organising principle or a literary form. All of the essays include a discussion of representative travel texts, to ensure that the volume as a whole represents a broad historical and geographical range of travel writing. Together, the 25 essays and the editors' introduction offer a comprehensive and authoritative reflection of the state of travel writing criticism and lay the ground for future developments.
Keywords: Travelers' writings -- History and criticism.; Travel writing -- History.; Écrits de voyageurs -- Histoire et critique.; Voyage -- Art d'écrire -- Histoire.; LITERARY CRITICISM -- General.; Travel writing; Travelers' writings; Electronic books.; Criticism, interpretation, etc.; History